DESIGN AND DEVELOPMENT OF AN AUTOMATIC FISH FEED AND WATER QUALITY MONITORING SYSTEM FOR WHATSAPP-BASED ORNAMENTAL FISH AQUARIUMS - Raya Frayos, Kornelius; Trias Pontia, F; Derdian Marindani, Elang (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Ornamental fish are one of several animals that are often in demand by many hobbyists, not infrequently some of them are willing to spend deeper than the aquarium to support the survival of fish for the sake of ornamental fish that are cared for always healthy. A healthy aquarium requires good care to maintain the survival of the fish and aquatic vegetation contained therein. In addition to the importance of regular fish feeding, water pH and water turbidity greatly determine water quality because they also determine chemical processes in water. In this study a control system was designed to provide fish feed automatically and remotely and monitor pH values, turbidity and water temperature in the aquarium. This tool is operated via Internet- based IoT, so it can monitor water quality and feed automatically via WhatsApp and Blynk. In this case WhatsApp and Blynk can monitor water quality and fish feeding remotely and remotely real-time. The data obtained can be accessed using the whatsapp and blynk applications. The pH 4502c sensor has an accuracy rate of 97.05%, the DS18B20 temperature sensor has an accuracy of 97.37%, and the SEN0189 turbidity sensor has an accuracy of 97.12%. The average response speed for sending replies to orders on WhatsApp is 4 seconds.